Effect of Chronic V.S. Intermittent Exposure to T-2 Toxin on Reproductive Performance in Bobwhite Quail - Grizzle, J.M.; Kersten, D.B.; Houston, A.E.; Saxton, A.M. (International Journal of Poultry Science, 2005)
Studies were conducted to determine the effect of chronic v.s. intermittent exposure to T-2 toxin on reproductive performance in adult bobwhite quail. In Experiment 1, 180 hens were orally dosed with 0% (LD0), 20% (LD20), 40% (LD40) or 60% (LD60) of the acute 100% lethal dose of T-2 toxin as determined in a previous experiment. One quarter of the dosage was administered each week for 3 weeks. Date of puberty was delayed 5 days as a result of the highest dose of T-2 toxin. There were no differences (P>0.05) in hen-day egg production or fertile hatchability of eggs as a result of intermittent exposure to T-2 toxin. Fertility and total hatchability of eggs collected from LD60 hens during week 2 following puberty were less (P 0.05) than from control hens. In Experiment 2, 139 hens were fed 0, 12, 16 and 20 mg T-2 toxin/kg feed for a 4 week period. Puberty was delayed 11 days among hens fed 20 mg/kg feed as compared to hens not fed T-2 toxin. Similarly, feed consumption was less (P < 0.05) among birds consuming any level T-2 toxin as compared to controls. No differences (P>0.05) in total hen-day egg production was found. However, percent fertility and total hatchability of eggs were lower (P